2020
DOI: 10.3390/ijms21020425
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Four Lytic Phages Infecting Klebsiella pneumoniae K22 Clinical Isolates from Spain

Abstract: The emergence of multi-drug-resistant bacteria represents a major public-health threat. Phages constitute a promising alternative to chemical antibiotics due to their high host specificity, abundance in nature, and evolvability. However, phage host specificity means that highly diverse bacterial species are particularly difficult to target for phage therapy. This is the case of Klebsiella pneumoniae, which presents a hypervariable extracellular matrix capsule exhibiting dozens of variants. Here, we report four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…This has been previously shown in other Klebsiella spp. [18] and in phages infecting other encapsulated bacteria, such as Escherichia coli or Acinetobacter baumannii [19,20]. The haloes of phage πVLC6 were wider than those of πVLC5, whereas lysed areas were larger for πVLC5, suggesting that these were two distinct phages.…”
Section: Isolation and Phenotypic Characterization Of Two New Klebsiementioning
confidence: 99%
See 1 more Smart Citation
“…This has been previously shown in other Klebsiella spp. [18] and in phages infecting other encapsulated bacteria, such as Escherichia coli or Acinetobacter baumannii [19,20]. The haloes of phage πVLC6 were wider than those of πVLC5, whereas lysed areas were larger for πVLC5, suggesting that these were two distinct phages.…”
Section: Isolation and Phenotypic Characterization Of Two New Klebsiementioning
confidence: 99%
“…Recently, our group has isolated and characterized four new phages of K. pneumoniae (πVLC1 to πVLC4) from environmental samples in Valencia, Spain [18]. All of these were closely related phylogenetically, belonged to the genus Drulisvirus, encoded only one depolymerase, and showed a very narrow capsular type range.…”
Section: Introductionmentioning
confidence: 99%
“…Morphology of plaques from Ganges water showed a halo around the clear zone, which might indicate depolymerase activity of KpG that could target the capsule of the strain (Fig. 1) (Domingo-Calap et al 2020). The phage displayed stability at the following pH 5.0, 7.0, 9.0, 11.0 with a survival rate of 86%, 100%, 91% and 77% respectively (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Another report showed that four lytic phages, belonging to the family Podoviridae, infecting K. pneumoniae capsular type K22, were isolated from environmental samples. They possessed narrow infectivity against a K. pneumoniae clinical isolates with K22 capsular type (Domingo-Calap et al 2020). In addition, the plaque morphology of the phages showed a halo around the lysis area, implying presence of depolymerase that lyses the capsule (Domingo-Calap et al…”
Section: Introductionmentioning
confidence: 99%
“…Morphology of plaques from Ganges water showed a halo around the clear zone, which might indicate depolymerase activity of KpG that could target the capsule of the strain (Fig. 1) (Domingo-Calap et al 2020).…”
Section: Resultsmentioning
confidence: 97%